A superhydrophobic and porous polymer adsorbent with large surface area. Issue 1 (17th December 2020) - Gong, Li; Wu, Wenhao; Lin, Daohui; Yang, Kun
Abstract : A superhydrophobic hypercrosslinked microporous polymer adsorbent, SHMP-1 was synthesized from 1, 3, 5-trinaphthylbenzene by cross-linking of methylene. SHMP-1 has the largest specific surface area of 2100 m 2 g −1 among superhydrophobic materials. Abstract : A superhydrophobic hypercrosslinked microporous polymer adsorbent, SHMP-1, with a water contact angle of 167° and an oil contact angle < 3°, was synthesized. SHMP-1 has a specific surface area of up to 2100 m 2 g −1, higher than the largest one ( i.e. 1618 m 2 g −1 ) reported for superhydrophobic materials. It is an amorphous polymer with a highly cross-linked structure of monomers linked by methylene, and consists of packed amorphous porous cells with pore channel widths of 5–19 Å. SHMP-1 can be stable up to 380 °C, and in organic solvents ( e.g. ethanol, acetone, carbon tetrachloride, tetrahydrofuran and n -hexane), HCl (5 mol L −1 ) and NaOH (5 mol L −1 ) solution. This polymer could be a promising adsorbent for absorption of organic solvents with capacities ranging from 4–25 times its own weight and capturing CO2 with an adsorption capacity of up to 6.02 mmol g −1 (273 K, 1 bar). Moreover, the CO2 adsorption capacity of SHMP-1 will not be decreased significantly (loss < 2.03%) by moisture even at a relative humidity of up to 90%, because of the surface superhydrophobicity.